Comprehensive analysis of m6A methylated modification of fibrotic atria in rats induced by chronic intermittent hypoxia - Geng, Tao; Qi, Shiyu; Cao, Xuan; Li, Jiao; Xia, Xiaodong; Gu, Tianshu; Wang, Hualing; Sun, Pengyu; Guan, Siyu; Shangguan, Wenfeng; Wang, Weiding; Zhang, Hao; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAtrial fibrosis serves as a key pathological basis for atrial fibrillation, significantly elevating the risk of cardiovascular events. However, its molecular mechanisms remain incompletely understood. N⁶-methyladenosine (m6A) modifications have been proven to involve in the pathological processes of cardiovascular diseases, yet its role in atrial fibrosis remains unclear. m6A plays an important role in disease pathogenesis via mRNA modification. This study aimed to define the role of m6A modifications in the fibrotic atria of rats with chronic intermittent hypoxia (CIH).MethodsA CIH model was established using rats living in an intermittent hypoxia simulation chamber filled with oxygen and nitrogen. Myocardial function and atrial fibrosis were examined by echocardiography, electrophysiology, and histopathology. Methylated RNA immunoprecipitation sequencing (MeRIP-Seq) and mRNA sequencing (mRNA-Seq) were performed on atria from control and CIH rats to identify differential m6A methylated genes and transcripts and further analyze their coexistence. Functional enrichment of the conjoint genes was analyzed using Gene Ontology and Kyoto Encyclopedia of Genes and Genomes assays. m6A distribution of the conjoint gene ANGPTL4 (angiopoietin like 4) was also observed. ANGPTL4 and m6A-related gene expression levels were determined by quantitative real-time polymerase chain reaction.ResultsCIH led to electrical conduction dysfunction and abnormal expression of fibrosis-associated proteins, indicating successful atrial fibrosis. Conjoint analysis identified 10 genes with upregulated m6A peaks and transcripts and 24 genes with downregulated m6A peaks and transcripts. These genes were functionally enriched in the calcium ion transport-related and fibrosis pathways (extracellular matrix receptor interaction). The m6A modification level of ANGPTL4 mRNA and the expression of four m6A regulatory enzymes were significantly different between control and CIH rats.ConclusionOur results revealed that m6A modification plays a crucial role in atrial fibrosis and may provide new therapeutic strategies for this disease.